2023
DOI: 10.3389/fvets.2023.1253151
|View full text |Cite
|
Sign up to set email alerts
|

Farmed fish welfare during slaughter in Italy: survey on stunning and killing methods and indicators of unconsciousness

Gianfilippo Alessio Clemente,
Clara Tolini,
Andrea Boscarino
et al.

Abstract: Information on slaughter procedures for farmed fish in aquaculture is limited, both in Europe and in Italy, due to a general lack of field data. The aim of this study was to gather information on the procedures used to slaughter fish in Italy and to discuss them considering the WOAH and EFSA recommendations on fish welfare. Using a questionnaire survey, data were collected by official veterinarians in 64 slaughtering facilities where 20 different species of fish were slaughtered. The main species slaughtered w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Indicators can include loss of righting reflex (equilibrium), vestibulo-ocular reflex (eye compensation for tilt), and ventilation. However, these indicators can be incredibly difficult to discern in a farm setting due to the pace at which large numbers of animals are processed, and have yet to be validated for sturgeon (Clemente et al, 2023). Following a stun, sturgeon are exsanguinated in a large container with a high density of fish, making indicators like loss of vestibulo-ocular reflex and loss of ventilation difficult to observe in individual fish.…”
Section: Discussionmentioning
confidence: 99%
“…Indicators can include loss of righting reflex (equilibrium), vestibulo-ocular reflex (eye compensation for tilt), and ventilation. However, these indicators can be incredibly difficult to discern in a farm setting due to the pace at which large numbers of animals are processed, and have yet to be validated for sturgeon (Clemente et al, 2023). Following a stun, sturgeon are exsanguinated in a large container with a high density of fish, making indicators like loss of vestibulo-ocular reflex and loss of ventilation difficult to observe in individual fish.…”
Section: Discussionmentioning
confidence: 99%
“…In Italy, a survey of 21 sea bass and sea bream farms found that none of the surveyed farms have adopted electrical stunning (Clemente et al, 2023). The slaughter methods used by the surveyed farms were "thermal shock" (20 farms) and "asphyxia in air" (one farm).…”
Section: Current Uptake Of Humane Slaughtermentioning
confidence: 99%
“…Fish producers believe that electrical stunning is more challenging for sea bass in particular, due to the fish getting stuck in the fish pumps leading to haemorrhages on their skin. A similar survey was conducted in Italy, but the negligible uptake of electrical stunning in the Italian sea bass and sea bream industry means that the survey did not produce detailed information about farmers' views on those species (Clemente et al, 2023).…”
Section: Industry Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation